Unveiling ZIF‑8 Nucleation Mechanisms through Molecular Simulation: Role of Temperature, Solvent, and Reactant Concentration - Sahar Andarzi Gargari (22675844) (2025)
Synthesizing new metal–organic frameworks (MOFs) is a challenging task, as the size, morphology, polymorph, and type and number of defects present on the synthesis product may depend on many variables, including temperature, solvent, concentration and nature of reactants, among others. A deeper understanding of how synthesis conditions determine the obtained material is crucial to optimize the use of resources when synthesizing new MOFs. In this contribution, we study the impact of changing concentration, solvent and temperature on the molecular level mechanisms of the solvothermal nucleation process of ZIF-8 relying on molecular dynamics simulations using a force field that incorporates metal–ligand reactivity. We find that the nucleation is faster when the synthesis is performed in dimethyl sulfoxide than when it is performed in methanol, in alignment with experimental observations. In the early steps of the nucleation process, we observe the formation of linear oligomers containing metal ions and ligands, which start forming cycles later on. All simulations lead to the formation of a final state that is highly connected and partially amorphous, which could be correlated to an intermediate species observed in direct experiments. The mechanism of formation of this phase mainly consists of the merging of smaller nuclei. Even though increasing temperature or reactant concentration lead to a similar nucleation speed-up, there are differences in ring populations and lifetimes within the highly connected amorphous intermediate phases formed in each case. Finally, important differences in the free energy of Zn–2-methylimidazolate versus Zn–imidazolate subsequent binding events are revealed and discussed. Interestingly, the free energy associated with subsequent binding events seems to be correlated with the formation of a larger variety of prenucleation building units in the case of imidazolate-based ZIFs, which could be at the onset of the existence of multiple polymorphs for this MOF.